Delivery of MGMT mRNA to glioma cells by reactive astrocyte-derived exosomes confers a temozolomide resistance phenotype. (1st October 2018) - Yu, Tianfu; Wang, XieFeng; Zhi, Tongle; Zhang, Junxia; Wang, Yingyi; Nie, Er; Zhou, Fengqi; You, Yongping; Liu, Ning
Abstract: The glioma-astrocyte interaction plays an important role in tumor microenvironment remodeling; however, the underlying mechanism has not been completely clarified. In this study, we show that glioma cells stimulate normal human astrocyte (NHA) into reactive astrocyte (RAS) in a non-contact manner. Additionally, the amount of O6-alkylguanine DNA alkyltransferase (MGMT) mRNA in exosomes (EXOs) released by RAS was significantly increased compared with that in non-reactive NHA. Importantly, MGMT-negative glioma cells can take up RAS-EXOs and acquire a temozolomide (TMZ)-resistant phenotype via the translation of exogenous exosomal MGMT mRNA both in vitro and in vivo. Our findings illuminate a novel phenomenon that may be a potent mechanism underlying glioma recurrence in which glioma-associated NHAs protect MGMT-negative glioma cells from TMZ-induced apoptosis by the functional intercellular transfer of exosomal MGMT mRNA. Highlights: Glioma cells stimulate normal astrocytes into reactive astrocytes via a non-contact way. Co-culture with astrocytes enhances the chemoresistance of glioma cells. Astrocyte-derived exosomal MGMT mRNA can be functionally translated into MGMT protein by recipient glioma cells.